(3dhGeY CfhGQ GdbdhH hLhGeY CSQGQ GdeMH hGdeMHhHs - (3YRjRj Hf YHO Gdedc Hf efUhQ GdLHdqj, CHh GdeYGdj, GdeYQha HTjPdI,J (B494 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj Ndb aGNJQY, hHOG aGHJOY heYdhe Cfg de JcJH gPg GdhKjbI EdG Yf bdH bQjM s
(3BNQgG (B:s
(3eHJhQ hBNQ GdehLhO efgG(B: (3hGdLeY Hjf ObGFb GdeYGfj hMSf GdYHGQGJ, hdcfj ecQg s
(3fSNI KGfjIs
(3JJab aj ChdgG eY GdfSNI GdChdi HGNJdGa aj HYV GdCdaGXs
(3hHChdgG Jedc eDQN SfI (B911(3g`s
(3hHgG fXGe GdJYbjHI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B275 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B232 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B381s
Keywords: (3GdCOHs